rezolvati ecuatia:
(x-3)^2-7(x-3)+12=0
Răspunsuri la întrebare
Răspuns de
1
(x-3)^2-7(x-3)+12=0
x^2-6x+9-7x+21+12=0
x^2-13x+42=0
Δ = 169 - 168 = 28
[tex] x_{1} = \frac{13- \sqrt{28}}{2} = \frac{13-2 \sqrt{7} }{2} x_{2} = \frac{13+ \sqrt{28}}{2} = \frac{13+2 \sqrt{7} }{2} [/tex]
x^2-6x+9-7x+21+12=0
x^2-13x+42=0
Δ = 169 - 168 = 28
[tex] x_{1} = \frac{13- \sqrt{28}}{2} = \frac{13-2 \sqrt{7} }{2} x_{2} = \frac{13+ \sqrt{28}}{2} = \frac{13+2 \sqrt{7} }{2} [/tex]
Alte întrebări interesante
Engleza,
9 ani în urmă
Chimie,
9 ani în urmă
Istorie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă